Emancipatory Dialectics: A Philosophical Analysis of the Tension between Kurdish Nationalism and Feminism in the Construction of Female Identity - Hassani, Shima (Sulaimani Journal for Humanities, 2025)
This research presents a philosophical analysis of the dialectical relationship between two emancipatory discourses - Kurdish nationalism and feminism - in the construction of Kurdish women's identity. Employing Hegelian dialectics as the overarching theoretical framework, this study conceptualizes Kurdish nationalism as thesis and feminism as antithesis, seeking to identify pathways toward a dynamic synthesis. Axel Honneth's Recognition Theory, through its tripartite distinction of love, rights, and social solidarity, provides a systematic framework for analyzing the multifaceted challenges faced by Kurdish women at each level. By incorporating Patricia Hill Collins's concept of intersectional consciousness into this framework, we demonstrate how the simultaneous experience of gender and national oppression can generate a unique form of critical consciousness that operates across all three levels of recognition.Adrienne Rich's politics of location helps us understand how this critical consciousness can be transformed into practical strategies for resistance and change. By connecting different levels of analysis - from the general dialectic between nationalism and feminism to the lived experience of Kurdish women within the three spheres of recognition - this research provides a theoretical framework for understanding and addressing these tensions. Furthermore, it demonstrates how this apparent contradiction can be utilized to develop new theoretical perspectives on the relationship between collective and individual emancipation
Keywords: Emancipatory Dialectics; Dynamic Synthesis; Recognition Theory; Intersectional Consciousness; Politics of Location